2015
DOI: 10.1111/neup.12212
|View full text |Cite
|
Sign up to set email alerts
|

SOX4 is overexpressed in diffusely infiltrating astrocytoma and confers poor prognosis

Abstract: The SOX4 (sex-determining region Y-related high-mobility-group box transcription factor 4) gene plays critical roles in embryonic development and cell-fate determination. Recently, SOX4 overexpression has been found in various tumors. However, its expression status and prognostic significance in astrocytoma remain unknown. In this study, SOX4 expression in diffusely infiltrating astrocytoma (WHO grades II-IV) tissues (in comparison with pilocytic astrocytomas) was examined by immunohistochemistry, and its rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
(58 reference statements)
1
3
0
Order By: Relevance
“…Other studies indicated that SOX4 was overexpressed in bladder tumor [48] and hepatocellular carcinoma [49] and it can regulate EMT to promote metastasis of cancer. In consistent with the former report concering SOX4 in glioma [50], we found SOX4 was upregulated in high grade glioma tissues compared with low grade ones, and the result showed that a positive correlation exists between H19 and SOX4. Furthermore, after koncking down H19 levels, SOX4 expression was significantly suppressed.…”
Section: Discussionsupporting
confidence: 81%
“…Other studies indicated that SOX4 was overexpressed in bladder tumor [48] and hepatocellular carcinoma [49] and it can regulate EMT to promote metastasis of cancer. In consistent with the former report concering SOX4 in glioma [50], we found SOX4 was upregulated in high grade glioma tissues compared with low grade ones, and the result showed that a positive correlation exists between H19 and SOX4. Furthermore, after koncking down H19 levels, SOX4 expression was significantly suppressed.…”
Section: Discussionsupporting
confidence: 81%
“…The role of SOX4 in glioma is controversial insofar as conflicting reports exist on SOX4 activity and expression, suggesting that its function may be context dependent. While some reports suggest that increased expression of SOX4 correlates with a favorable prognostic outcome, others suggest poor overall prognoses associated with high expression ( de Bont et al, 2008 ; Li et al, 2015 ). In human glioma cell lines, SOX4 inhibits growth by influencing WNT and TGF signaling pathways, as well as p53-p21 activity ( Zhang et al, 2014 ).…”
Section: Lineage-specific Transcriptional Regulatorsmentioning
confidence: 99%
“… 3 , 4 , 5 , 6 Overexpression and amplification of SOX4 have been implicated in various cancers and are correlated with poor prognosis. 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 In mouse models, previous studies demonstrated that the upregulation of Sox4 can be induced by and then cooperate with the aberrant expression of AML1-ETO , 17 NUP98-DDX10 (ref. 18 ) and PML-RARa ; 19 the overexpression of HOXA9 (ref.…”
Section: Introductionmentioning
confidence: 99%